Studies On The Materiality And Aggregation, Compensation And Offsetting In Financial Statements - GADAU, Liana (Annals of Spiru Haret University. Economic Series, 2016)
The accounting principles should be considered an essential element in the preparation and presentation of financial statements, with our analysis focusing especially on the relative principles: Materiality and aggregation, compensation and offsetting. We consider necessary to improve the analyzed concepts by bringing additional information, as clear and comprehensive as possible, information used as reference in the preparation of financial statements. Moreover, is crucial to apply an unitary thinking of the accounting referential which is linked to these accounting principles. The research methods used in analyzing the principles are: documentation of theoretical study of normative acts in the field of accounting, observation, comparative analysis, synthesis, information classification and data interpretation.